Mesenchymal Stromal Cells From Emphysematous Donors and Their Extracellular Vesicles Are Unable to Reverse Cardiorespiratory Dysfunction in Experimental Severe Emphysema - Antunes, Mariana A.; Braga, Cassia L.; Oliveira, Tainá B.; Kitoko, Jamil Z.; Castro, Ligia L.; Xisto, Debora G.; Coelho, Mariana S.; Rocha, Nazareth; Silva-Aguiar, Rodrigo P.; Caruso-Neves, Celso; Martins, Eduarda G.; Carvalho, Clara Fernandes; et al. (Frontiers in Cell and Developmental Biology, 2021)
Although bone marrow-derived mesenchymal stromal cells (BM-MSCs) from patients with chronic obstructive pulmonary disease (COPD) appear to be phenotypically and functionally similar to BM-MSCs from healthy sources in vitro, the impact of COPD on MSC metabolism and mitochondrial function has not been evaluated. In this study, we aimed to comparatively characterize MSCs from healthy and emphysematous donors (H-MSCs and E-MSCs) in vitro and to assess the therapeutic potential of these MSCs and their extracellular vesicles (H-EVs and E-EVs) in an in vivo model of severe emphysema. For this purpose, C57BL/6 mice received intratracheal porcine pancreatic elastase once weekly for 4 weeks to induce emphysema; control animals received saline under the same protocol. Twenty-four hours after the last instillation, animals received saline, H-MSCs, E-MSCs, H-EVs, or E-EVs intravenously. In vitro characterization demonstrated that E-MSCs present downregulation of anti-inflammatory (TSG-6, VEGF, TGF-β, and HGF) and anti-oxidant (CAT, SOD, Nrf2, and GSH) genes, and their EVs had larger median diameter and lower average concentration. Compared with H-MSC, E-MSC mitochondria also exhibited a higher respiration rate, were morphologically elongated, expressed less dynamin-related protein-1, and produced more superoxide. When co-cultured with alveolar macrophages, both H-MSCs and E-MSCs induced an increase in iNOS and arginase-1 levels, but only H-MSCs and their EVs were able to enhance IL-10 levels. In vivo, emphysematous mice treated with E-MSCs or E-EVs demonstrated no amelioration in cardiorespiratory dysfunction. On the other hand, H-EVs, but not H-MSCs, were able to reduce the neutrophil count, the mean linear intercept, and IL-1β and TGF-β levels in lung tissue, as well as reduce pulmonary arterial hypertension and increase the right ventricular area in a murine model of elastase-induced severe emphysema. In conclusion, E-MSCs and E-EVs were unable to reverse cardiorespiratory dysfunction, whereas H-EVs administration was associated with a reduction in cardiovascular and respiratory damage in experimental severe emphysema.